Estudo de variabilidade da frequência cardíaca por meio da análise espectral em idosos: estudo comparativo entre pacientes sem e com Hipotensão postural - Carlos Eduardo de Souza Miranda (2015)
The prevalence of orthostatic hypotension (OH) increases with age and is related, among other factors, with changes in autonomic regulation of blood pressure (BP) and heart rate (HR). Its clinical manifestations cause significant functional impairment in the elderly population and, even in asymptomatic individuals, the HO is associated with increased mortality. The analysis of the autonomic nervous system (ANS), which is involved in the pathophysiology of HO, can be performed from the measurement of spectral analysis of heart rate variability (HRV) and its components. The primary objective of this study was to evaluate the ANS behavior through the spectral analysis of HRV in elderly patients with HO and compare with the HRV spectral analysis in elderly without OH. Methods: We evaluated 105 patients (39 patients with HO, constituting the case group, and 66 without HO, constituting the control group) aged over 60 years, consecutively enrolled from September 2012 to December 2014. The evaluation was performed through clinical examination, resting electrocardiogram and spectral analysis of HRV (by Fourier transformation), obtained from recordings by digital Holter. Results: The mean age of patients was 71.9 years, 64 patients (61%) were female. BP means in the supine and standing positions were 140.3/81.7 mmHg and 132/78.8 mmHg, respectively; and the average HR were 67.6 beats per minute (bpm) and 72.5 bpm, respectively. The most prevalent cardiovascular risk factors were hypertension, present in 80 patients (76.9%), and dyslipidemia, present in 42 patients (40%). Thiazide diuretics were the antihypertensive drugs most used, alone or in combination with other antihypertensive medications. When comparing the HRV components of the entire population, in supine and standing, there was a significant reduction in mean HF component (620.5 versus 480.7 ms2, p = 0.001) and increased in mean ratio LF/HF (2.5 versus 4.0 ms2, p <0.001), with no change in mean LF component (534.8 versus 381.0 ms2, p=0.080). When compared case and control groups, there was the following variables related difference: average HR in the supine (62.6 versus 70.6 bpm, p = 0.001) and standing (68.2 versus 75.0 bpm, p=0.006); use of inhibitors of angiotensin converting enzyme (41% versus 21.2%, p=0.030); occurrence of symptoms (77% versus 51.5%, p=0.001); as compared to total cholesterol, LDL cholesterol and triglycerides, which on average were smaller in the case group (p=0.002; p=0.007; p=0.034, respectively). There was no difference related to BP in the supine position and the groups were matched for age and gender. Regarding the HRV components, there were differences between the groups, just as the LF component of the average in the supine position (331.1 case group versus 647.6 ms2 control group, p=0.014). By multivariate analysis, the HR in the supine position was the independent variable for the occurrence of HO (p = 0,001- 95% CI= - 0.022 and -0.006). For the receiver operating characteristics, the best cut point for FC was 61 bpm, with 77.3% sensitivity, 51.3% specificity, positive predictive value of 61.3%, and negative predictive value of 69.3%. Conclusions: In this elderly population, there was a lower average value of the LF component and HR in supine position in patients with OH, without gender influence. The independent predictor of OH was the FC in supine position, which presented an odds ratio of 3.23 when was above 61 bpm. Key-words: hypotension orthostatic, aged, heart rate.